Investigation of antimalarial activity of crude Malaysian stingless bee propolis - Yusoff, Nur Fatin Ayunni (Universiti Sains Malaysia, 2017)
Malaria is a mosquito-bome disease that is caused by plasmodium species and killed nearly 429, 000 people in 2015. With the emergence of plasmodium drug-resistance, many studies are conducted to find a new drug to treat malaria. Furthermore, with the resurgence of traditional medicine that is used to treat various disease nowadays, propolis as one of the traditional medicine recorded to possess many medicinal values including antimalarial property. Propolis is the resinous mixture produced by bees from the resin that collected from the surrounding plants. Bees use propolis to protect its hives from an external intruder by patching the propolis on the crack or the opening of the hive. However, there is a very limited study on the Malaysian stingless bee propolis (Trigona itama) on its antimalarial property. Therefore, this study was aimed to investigate the antimalarial activity of Malaysian stingless bee propolis. The results of in vitro SYBR Green I-based fluorescence assay against Chloroquine-sensitive Plasmodium falciparum (3D7) showed both water extract (WEP) and ethanol extract (EEP) do not possess antimalarial activity. The result is concordance with the very low level of total phenolic content (WEP; 16.4 ± 0.001 mg GAE/g and EEP; 31.3 ± 0.004 mg GAE/g) and total flavonoid content (WEP; 30 mg QE/g and EEP, n,d) isolated from the extracts. As this is a preliminary study on looking antimalarial property of Malaysian propolis, therefore there is a need to do another study to confirm the result.